If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 25 = 79 Reorder the terms: 25 + 2x = 79 Solving 25 + 2x = 79 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 2x = 79 + -25 Combine like terms: 25 + -25 = 0 0 + 2x = 79 + -25 2x = 79 + -25 Combine like terms: 79 + -25 = 54 2x = 54 Divide each side by '2'. x = 27 Simplifying x = 27
| Tan(5x-10)=0 | | 4x^2+7x-36= | | -5/5=-7/10x | | 3x/2=18 | | 18t=12t+3 | | cos(x)/4cos(x) | | 7x/8=7 | | n+-6=9 | | 5b-4=13 | | X/7-9=5 | | -9(x+2)-6=-24 | | 300+20logx=60 | | 6x^2+10x-102=0 | | 30=1.5r+6 | | 5z-5=8z-4z | | -7(5)+y=4 | | 45/900 | | (2+y)i+3x=12+5i | | -7(2)+y=4 | | 7f+8=k | | 10b/b-a | | 7x+6=3x-38 | | 4t-7t=7-2t-5 | | 5w=500 | | -7(-2)+y=4 | | 5x-10+(8x-5)=180 | | 3x/6-54=-5 | | 7x-5=3+11 | | 7/9×4/9= | | 3x+8+2x+48=90 | | 15=d-6 | | 48=8x^2 |